Artificial nightlight alters the predator–prey dynamics of an apex carnivore. Issue 2 (18th October 2020) - Ditmer, Mark A.; Stoner, David C.; Francis, Clinton D.; Barber, Jesse R.; Forester, James D.; Choate, David M.; Ironside, Kirsten E.; Longshore, Kathleen M.; Hersey, Kent R.; Larsen, Randy T.; McMillan, Brock R.; Olson, Daniel D.; et al.
Abstract : Artificial nightlight is increasingly recognized as an important environmental disturbance that influences the habitats and fitness of numerous species. However, its effects on wide‐ranging vertebrates and their interactions remain unclear. Light pollution has the potential to amplify land‐use change, and as such, answering the question of how this sensory stimulant affects behavior and habitat use of species valued for their ecological roles and economic impacts is critical for conservation and land‐use planning. Here, we combined satellite‐derived estimates of light pollution, with GPS‐data from cougars Puma concolor (n = 56), mule deer Odocoileus hemionus (n = 263) and locations of cougar‐killed deer (n = 1562 carcasses), to assess the effects of light exposure on mammal behavior and predator–prey relationships across wildland–urban gradients in the southwestern United States. Our results indicate that deer used the anthropogenic environments to access forage and were more active at night than their wildland conspecifics. Despite higher nightlight levels, cougars killed deer at the wildland–urban interface, but hunted them in the relatively darkest locations. Light had the greatest effect of all covariates on where cougars killed deer at the wildland–urban interface. Both species exhibited functional responses to light pollution at fine scales; individual cougars and deer with less light exposure increasingly avoided illuminated areas when exposed to greater radiance, whereas deer living in the wildland–urban interface selected elevated light levels. We conclude that integrating estimates of light pollution into ecological studies provides crucial insights into how the dynamic human footprint can alter animal behavior and ecosystem function across spatial scales.